2007
DOI: 10.1002/eji.200737532
|View full text |Cite
|
Sign up to set email alerts
|

Critical role for Ipaf in Pseudomonas aeruginosa‐induced caspase‐1 activation

Abstract: Pseudomonas aeruginosa is an opportunistic Gram-negative human pathogen that is responsible for a broad range of infections in individuals with a variety of predisposing conditions. After infection, P. aeruginosa induces a marked inflammatory response in the host. However the mechanisms involved in bacterium recognition and induction of immune responses are poorly understood. Here we report that the Nod-like receptor family member Ipaf is required for optimal bacterial clearance in an in vivo model of P. aerug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
245
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(264 citation statements)
references
References 54 publications
14
245
2
3
Order By: Relevance
“…While this article was in preparation, other groups also showed that P. aeruginosa activates caspase 1 through Ipaf, T3SS, and flagellin. Some T3SS effectors may modulate this process (30)(31)(32). More than 90% of environmental P. aeruginosa isolates express both flagellin and the Psc T3SS (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…While this article was in preparation, other groups also showed that P. aeruginosa activates caspase 1 through Ipaf, T3SS, and flagellin. Some T3SS effectors may modulate this process (30)(31)(32). More than 90% of environmental P. aeruginosa isolates express both flagellin and the Psc T3SS (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Although ASC is required for activation and secretion of IL-1β and IL-18 downstream of the Nlrc4 inflammasome, it is dispensible for activation of host cell death (Fig. 2B) (28). Therefore, to determine if IL-1β and IL-18 were required for attenuation of L. monocytogenes-L.p.FlaA, we assayed virulence in ASC −/− mice.…”
Section: Monocytogenes Ectopically Expressing Flagellin Hyperactivatementioning
confidence: 99%
“…47 Similarly, recently published data show that Pseudomonas aeruginosa requires both Ipaf and ASC to induce IL-1b secretion, but that ASC is dispensable for inducing pyroptosis. 51,86 Conversely, ASC has been shown to induce pyroptosis in the human monocytic THP-1 cell line, engineered to express a GFP-tagged ASC. Upon stimulation with inflammatory agonists, ASC was shown to oligomerize into a single cytoplasmic 'pyroptosome' required for caspase-1 activation and induction of pyroptosis.…”
Section: Activators Of Pyroptosis: the Inflammasomes And Pyroptosomementioning
confidence: 99%
“…41,49,52,56,66 In some cases, the effector molecule responsible for caspase-1 activation has been identified. For the flagellated bacteria Salmonella typhimurium, 82,83 Legionella pneumophila, 54 and Pseudomonas aeruginosa, 86,91 proper expression of flagellin is required for caspase-1 activation. In addition, purified flagellin is also able to induce caspase-1 activity if introduced into the cytosol through cationic lipids such as DOTAP.…”
Section: Modulation Of Caspase-1 Activitymentioning
confidence: 99%
See 1 more Smart Citation